Collaborating for Excellence, Strengthening Clinical Trials in Pakistan - Editorial Commentary - Sadia Hassan; Saeed Hamid; Zeba Aziz; Arishay Hussaini; Javed Akram; Irfan Ahmed (PKLI Journal of Health Sciences, 2026)
Pakistan, the world’s fifth most populous country, has immense clinical research potential given its diverse population and high disease burden, particularly in endocrinology, neurology and cardiology. Progress, however, is constrained by inconsistent ethical review, weak infrastructure, and limited resources. Strengthening clinical trials requires training, strong governance, incentives for faculty, industry partnerships, and patient and public involvement. In July 2025, Pakistan Kidney and Liver Institute and Research Center hosted a national seminar to explore cross-collaboration and capacity building. The seminar’s overarching goal was to highlight the importance of cross-collaboration and explore opportunities to enhance trial governance and capacity building. It aimed to coalesce discussions into a consensus statement that could guide national strategies for the ethical and efficient conduct of clinical trials in Pakistan.